2021
DOI: 10.7554/elife.62483
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation inhibits IGF-1 signaling and confers methionine restriction-like healthspan benefits to mice

Abstract: Methionine restriction (MR) dramatically extends the healthspan of several organisms. Methionine-restricted rodents have less age-related pathology and increased longevity as compared with controls, and recent studies suggest that humans might benefit similarly. Mechanistically, it is likely that the decreased IGF-1 signaling that results from MR underlies the benefits of this regimen. Thus, we hypothesized that interventions that decrease IGF-1 signaling would also produce MR-like healthspan benefits. Seleniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…show reduced insulin (but not glucose) levels in response to continuous MR (Plummer et al, 2021), a finding that is reproduced in the current study (Figure 4e). It is therefore notable that females undergoing the IMR2 regimen maintained relatively low blood glucose levels, the same as males undergoing either intermittent or continuous MR (Figure 2e).…”
Section: Interestingly We Have Previously Observed That Female Mice Onlysupporting
confidence: 88%
See 3 more Smart Citations
“…show reduced insulin (but not glucose) levels in response to continuous MR (Plummer et al, 2021), a finding that is reproduced in the current study (Figure 4e). It is therefore notable that females undergoing the IMR2 regimen maintained relatively low blood glucose levels, the same as males undergoing either intermittent or continuous MR (Figure 2e).…”
Section: Interestingly We Have Previously Observed That Female Mice Onlysupporting
confidence: 88%
“…While it is known that continuous MR both protects against liver steatosis and results in smaller sized livers (Ables et al, 2012 ; Malloy et al, 2013 ; Yang et al, 2019 ), we recently observed that another healthspan‐promoting dietary intervention ( i . e ., selenium supplementation) operates similarly in that it has a robust anti‐adiposity effect and produces smaller livers as compared with controls (Plummer et al, 2021 ). However, IMR only has the former activity, as liver mass was not significantly affected by this regimen (Figure 1g , Figure S3c ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapeseed has diverse types of glucosinolates which vary greatly within rapeseed varieties, and thus rapeseed has great potential for genetic improvement [ 21 ]. Selenium, one of the essential elements for human body, is recognized as a “longevity element” [ 22 ]. Selenium-rich food is one of the main pathways for humans to obtain organic selenium.…”
Section: Introductionmentioning
confidence: 99%